Accessibility and the role of the consideration set in spatial choice modelling: A simulation study - Ari Pramono; Harmen Oppewal (Journal of Choice Modelling, 2012)
A recurring issue in the discourse about choice modelling is the role of consideration sets. Many scholars have proposed that consumers will follow a twostage decision process. This paper argues that in spatial choice contexts the role of the consideration set may largely depend on the decision maker's level of access to the alternatives. It is proposed that in conditions where the decision maker's accessibility toward alternatives is constrainedfor example as a result of time space feasibilitya two-stage model will perform better than a on-stage model. The more restrictive the constraints, the more important the role of the consideration set. The paper presents a simulation analysis of the effects of geographical accessibility on consideration and choice in the context of motorists' decisions where to refuel. It simulates a grid road network where the motorists' access to petrol stations is constrained by the geographical location of the alternatives, the availability of network connections between them and the decision makers' time budgets. In this hypothetical spatial environment the study simulates consideration and choice processes for refuelling options under different conditions of petrol station access, (non-spatial) station attractiveness, and heterogeneity in the decision maker's time budget.
Keywords: 330; spatial choice; consideration sets; accessibility